2005
DOI: 10.1105/tpc.105.037507
|View full text |Cite
|
Sign up to set email alerts
|

ROR1/RPA2A, a Putative Replication Protein A2, Functions in Epigenetic Gene Silencing and in Regulation of Meristem Development inArabidopsis

Abstract: We screened for suppressors of repressor of silencing1 (ros1) using the silenced 35S promoter-neomycin phosphotransferase II (Pro 35S :NPTII) gene as a marker and identified two allelic mutants, ror1-1 and ror1-2 (for suppressor of ros1). Mapbased cloning revealed that ROR1 encodes a 31-kD protein similar to DNA replication protein A2 (RPA2A). Mutations in ROR1 reactivate the silenced Pro 35S :NPTII gene but not RD29A promoter-luciferase in the ros1 mutant. DNA methylation in rDNA, centromeric DNA, and RD29A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(124 citation statements)
references
References 87 publications
(126 reference statements)
9
114
1
Order By: Relevance
“…However, pold2-1 had little effect on the ProRD29A:LUC locus in dms3-4. Like mutants of DNA replication-related proteins (Elmayan et al, 2005;Xia et al, 2006;Yin et al, 2009;Liu et al, 2010aLiu et al, , 2010b, pold2-1 failed to suppress the silenced ProRD29A:LUC in the ros1-1 mutant (Fig. 1F).…”
Section: Isolation Of a New Component In The Drr-tgs Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…However, pold2-1 had little effect on the ProRD29A:LUC locus in dms3-4. Like mutants of DNA replication-related proteins (Elmayan et al, 2005;Xia et al, 2006;Yin et al, 2009;Liu et al, 2010aLiu et al, , 2010b, pold2-1 failed to suppress the silenced ProRD29A:LUC in the ros1-1 mutant (Fig. 1F).…”
Section: Isolation Of a New Component In The Drr-tgs Pathwaymentioning
confidence: 99%
“…1C). TSIs are endogenous TGS loci (Steimer et al, 2000), the expression of which is altered in some mutants involved in DNA methylation, histone modification, or DNA replication (Steimer et al, 2000;Xia et al, 2006;Yin et al, 2009;Liu et al, 2010aLiu et al, , 2010b. The expression of TSIs was increased in these isolated mutants (Fig.…”
Section: Isolation Of a New Component In The Drr-tgs Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…AtRPA1a is required for interference-sensitive crossover formation but dispensable for meiotic DSB repair (Osman et al, 2009), and the atrpa1b (At5g08020) mutant is indistinguishable from wild type under normal conditions but is hypersensitive to MMS and UV-B (Ishibashi et al, 2005). In addition, mutant plants with one of the AtRPA2 subunits (At2g24490) are smaller than wild type and the transcriptional gene silencing is suppressed in a DNAmethylation-independent manner (Elmayan et al, 2005;Kapoor et al, 2005;Xia et al, 2006), indicating that these individual RPA subunits have different functions in Arabidopsis DNA metabolism.…”
Section: Functional Diversification Of Rpa1s In Arabidopsis and Ricementioning
confidence: 99%
“…Moreover, studies with mutant plants revealed that Arabidopsis RPA1A and RPA1C (nuclear proteins) are essential for DNA replication, whereas RPA1B (chloroplast and nuclear) is not essential and is required only during DNA repair (Sakaguchi et al 2009). Apart from its function in DNA replication, RPA2 is also required to maintain transcriptional silencing of a subset of transposon elements (Elmayan et al 2005;Kapoor et al 2005;Xia et al 2006). …”
Section: Rpamentioning
confidence: 99%